Saving energy by changing the tariff structure and applying flag fees in Brazil - Touma, Daniela Wolter Ferreira; Cassula, Agnelo Marotta [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Trying to mitigate the crisis in the energy sector in the last few years, the Brazilian government implemented tariff flags, which increase the power bills in several areas. Alternative analyses of the power consumption may suggest ways to reduce losses and the monthly power bill. This paper identifies the different strategies of power billing in a residential and a small industrial consumer in Brazil. It uses power measurements in the two different consumers in detail to propose improvements in the consumption which could lead not only to decrease the power bill but also to relieve the power energy system.
Keywords: Brazil; Energy consumption; Power System; Pricing; Tariff